Use of Nonabsorbable Spiral Tacks for Mesh Reinforcement in Thoracoscopic Repair of Congenital Diaphragmatic Hernia - Poupalou, Anna; Vrancken, Celine; Vanderveken, Erwin; Steyaert, Henri (European Journal of Pediatric Surgery Reports, 2018)
Thoracoscopic prosthetic repair of congenital diaphragmatic hernia (CDH) is a well-established and safe technique in experienced hands but the patching procedure is technically demanding and time consuming. To address the challenges associated with this process (confined working space and restricted time), the aim of this article is to assess the potential improvements in feasibility, efficacy, and safety of patch fixation by using nonabsorbable helicoidal tacks in neonates and infants for the repair of large CDH by thoracoscopy. The new technique has all the advantages of minimal invasive surgery in very young children combined with the advantages of reduced operating time and increased simplicity, and may be a good option in cases of recurrence.
Keywords: diaphragmatic hernia; thoracoscopy; patch; tack